Three-dimensional modelling of a tidal channel: The Espinheiro Channel (Portugal) - Vaz, N.
A 3D baroclinic model (Mohid) is used to perform hindcast simulations in a tidal channel: the Espinheiro Channel (Portugal). These simulations are conducted for four distinct periods where markedly different river discharge and tides occurred, and the outputs are compared to time series measurements and synoptic thermohaline data. The model reveals its ability in reproducing observed temporal variability in sea level height and along-channel velocity, presenting skill coefficients higher than 0.85. The model qualitatively reproduces along-channel thermohaline distributions at three different vertical levels, during low-to-medium river inflow, underestimating the salinity stratification when the river flow is high (higher than View the MathML source). In general, the trends inferred from the observations are reproduced by the numerical model. The cross-sectional tidally averaged structure of salinity and longitudinal velocity analyzed near the channel's mouth reveals ebb residual currents at the south shore and flood residual currents at the north shore under low-to-medium river discharge. When the river discharge is high (higher than View the MathML source), the channel is almost laterally homogeneous in terms of salinity and residual velocity presenting a two-layer structure with flood currents near the bottom and ebb currents at the top layer. The salt transport was also analyzed and follows the same patterns found in the cross-sectional residual velocity. Close to the channel's mouth, the water exchange is mainly driven by the tidal forcing, except under high river flow events when the freshwater extends its influence from the channel's head to its mouth.